Does attachment to parents and peers influence health literacy among adolescents in Malaysia? - Hamzah, Siti Raba’ah; Ismail, Maimunah; Mohd Nor, Zanariah (Faculty of Health and Social Sciences, University of South Bohemia, 2018)
Despite extensive research on the impact of social factors on the health literacy of adolescents, few studies have investigated how attachment to parents and peers influences adolescents’ level of health literacy. Adolescence is generally viewed as the period of life before adulthood, and during this phase, young persons are dependent on the support of their parents and peers. This study was conducted in response to the gap in the research regarding the influence of parental and peer attachment on the health literacy of adolescents. The participants in this study comprised a random sample of adolescents aged 15–17 years, who were residents of the Klang Valley, a highly urbanized region in Malaysia. The study found that the level of health literacy among these adolescents was moderate (M = 3.61, SD = 0.51 on a scale of 5). While the level of peer attachment among them was moderate (M = 3.48, SD = 0.58), the level of parental attachment was high (M = 3.73, SD = 0.83 on a scale of 5). Both parental attachment (β = 0.30, p < 0.05) and peer attachment (β = 0.37, p < 0.05) were shown to have significant independent effects on the level of adolescents’ health literacy. Together, parental attachment and peer attachment explained 30% of the variance in health literacy among adolescents.